Anti-Depopulation Policy as a Method for Boosting Russia’s National Security - Vladimirovna Gnezdova, Julia; Iosifovich Deren, Vasiliy; Nikolaevna Rudakova, Elena; Vladimirovna Karapetyants, Irina; Anatolievna Safronova, Anastasia (International Journal of Engineering and Technology, 2018)
This paper makes a case for that declines in population size must be counteracted via a well-substantiated anti-depopulation policy. Russia’s current anti-depopulation policy has yet to live up to its potential. The linkage between depopulation and social/economic processes taking place across the Russian Federation may well be associated with the nation’s rather inhomogeneous, polarized natural-terrain, territorial-economic, and settlement structure and marked differentiation in terms of major demographic and natural/economic determinants. By its subject matter, the issue of depopulation has long stopped being strictly scientific – it now also has a political, economic, and ethnocultural ring to it. In this context, ‘The Concept on Demographic Policy in the Russian Federation for the Period through to 2025’ expressly sets out the goals, principles, objectives, and key focus areas for Russia’s demographic policy, as well as the mechanisms for implementing it and curbing depopulation. However, all these postulates have thus far failed to be a factor for rational activity and greater responsibility for implementing set objectives on the part of relevant public authorities, which is affecting the nation’s geopolitical security.